Hansi ki kahaniyan - Maqbool jhangir (Ferozesons; Lahore, 2002)
"Hansi Ki Kahaniyan" by Maqbool Jhangir is a delightful collection of humorous and entertaining stories that offer light-hearted reflections on life, weaving wit and satire into everyday situations to evoke laughter and joy.